Two-Stroke Thermodynamic Cycle Optimization of a Single-Cylinder Free-Piston Engine Generator - Houliang Yu; Zhaoping Xu; Qinglin Zhang; Liang Liu; Ru Hua (Advances in Materials Science and Engineering)
A free-piston engine generator (FPEG) is a new type of energy converter, which eliminates the crankshaft and connecting rod mechanism. In order to achieve efficient energy conversion, the two-stroke thermodynamic performance optimization of a single-cylinder free-piston engine generator is investigated in this paper. Firstly, the components, four-stroke thermodynamic cycle, two-stroke thermodynamic cycle, and prototype system of the FPEG are presented in detail. The one-dimensional flow simulation model of the FPEG is created based on the gas dynamics equation, Weber combustion function, and heat transfer function, and then the model is validated by the data tested from the prototype system. According to the four-stroke experimental results of the FPEG, an effective power of 4.75 kW and a peak pressure of 21.02 bar have been obtained. Then, the two-stroke thermodynamic cycle is simulated and compared under the different control parameters of intake air pressure, injection timing, ignition timing, and valve timing through the simulation model. The optimized results show that an indicated thermal efficiency of 27.6%, an indicated power of 6.7 kW, and a maximal working frequency of 25 Hz can be achieved by the prototype system, when the two-stroke thermodynamic cycle is used.